Influence of Compliant Joints in Four-Legged Robots - Spadaro, Francesco Tracuzzi; Muscolo, Giovanni Gerardo (Frontiers in Mechanical Engineering, 2020)
Legged animals are capable of rapid movements, are efficient from the energy point of view and are able to adapt gaits to environmental conditions. Motions like walking, trotting, galloping and jumping, are difficult to evaluate and replicate due to their being consequence of tricky interaction of different systems (like the musculoskeletal system and the central and peripheral nervous systems, including also the influence of the environment). In this paper, we analyzed the behaviour of a four-legged robot constituted by 1 active DOF in each leg (using commercial servomotors) and 1 passive DOF in each knee and in spine (using springs). Our objective is to increase the motion performances of the robot varying the stiffness of the springs. The results obtained from the simulation underline how the stiffness of the spine influences the performance of the robot by increasing the speed and reducing the energy requested by the servomotors.